Nonconvexity in General Equilibrium Labor Markets - Coles, Jeffrey L. (Journal of Labor Economics, 1986)
The classic case of nonconvexity in consumer opportunities is that of labor supply. While most studies of labor supply concentrate on the individual agent in partial equilibrium, this study considers general equilibrium. I show that even with nonconvex consumer opportunites, such as those involved in the labor supply decision, the standard theorems of general equilibrium models still hold.